Implementation of The Parents and Teachers’ Initiatives in Teaching Grade 1 Learners in Phonetic Blending Amidst Covid-19 Pandemic - Manguilimotan, Ramil P.; Padillo, Gengen G.; Bustillo, Maria Richiel; Quilaton, Engel C.; Pajares, Noime P.; Capuno, Reylan G.; Villarin, Eric R. (International Journal of Social Sciences and Humanities Invention, 2023)
This research determined the implementation of the parents’ and teachers’ initiatives in teaching Grade 1 learners phonetic blending in the public elementary school in Cebu during the School Year 2020-2021 as the basis for a home reading action plan. It utilized the adapted descriptive-comparative research design using survey questionnaires and supported interviews to gather data. The respondents are 84 learners with phonetic blending difficulty, 29 Grade 1 teachers, and 231 parents. Collected data were statistically treated using frequency, percentage, weighted mean, and rank. Results showed that parent-respondents are mostly 29-35 years old, female, high school graduates, dominated by mothers, available materials at home are books and grandmothers as other learning adults at home. Teacher-respondents are all females, under 29-40 years old, with masteral units, teacher III and taught for more than ten years. Parents perceived the level of learners’ phonetic blending ability as skilled and less skilled for teachers.Moreover, the level of implementation of the respondent groups’ initiatives in the development of the learners’ phonetic blending abilities is perceived as implemented for parents and highly implemented for teachers. Results show that the parents’ and teachers’ perceptions are significant. Lastly, the extent of the problems encountered by the respondents is found to be high for parents and teachers. Hence, it is concluded that both respondent groups differ in implementing initiatives in phonetic blending during the pandemic. Adoption of the home reading action plan is recommended.